OECD 국가별 아크용접로봇과 저항스폿용접로봇의 최소자승법에 관한 연구 - 안덕현(Duck-Hyun An); 김옥환(Ok-Hwan Kim) (한국생산제조학회지, 2024)
The purpose of this study is to investigate the average annual market growth rate of welding robots currently being performed worldwide using the least square method for arc welding robots and resistance spot welding robots by OECD countries. To conduct this study, we will compare and analyze the differences between arc welding robots and resistance spot welding robots in OECD countries such as the US, EU, Japan, China, and Korea. The global welding robot market is dominated by arc welding robots and resistance welding robots, and resistance welding robots have a relative advantage over arc welding robots, and the gap between the two welding robot markets is gradually widening. In particular, we review existing studies on welding robots in OECD countries, analyze them by applying the least square method of time series analysis, diagnose the problems of existing studies, and suggest future research directions. KCI Citation Count: 0